Today’s Youth and Mental Health Hope, Power, and Resilience - Pashang, Soheila; Khanlou, Nazilla; Clarke, Jennifer (Advances in Mental Health and Addiction, 2018)
XXXVI, 436 p. 21 illus., 17 illus. in color.